so sánh 5 và\(\sqrt{3+1}\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
2) \(4=\sqrt{16}\)
\(2\sqrt{5}=\sqrt{20}\)
mà 16<20
nên \(-4>-2\sqrt{5}\)
3) \(3\sqrt{5}=\sqrt{45}\)
\(6=\sqrt{36}\)
mà 45>36
nên \(-3\sqrt{5}< -6\)
\(5-\sqrt{5}.\sqrt{3}=5-\sqrt{5.3}=5-\sqrt{15}\)
\(1=5-4=5-\sqrt{16}\)
-Vì \(-\sqrt{15}>-\sqrt{16}\) nên \(5-\sqrt{15}>5-\sqrt{16}\)
\(\Rightarrow5-\sqrt{5}.\sqrt{3}>1\)
Đặt:
\(A=\sqrt{3+\sqrt{5}}+\sqrt{3-\sqrt{5}}\)
\(A=\dfrac{1}{\sqrt{2}}\left(\sqrt{6+2\sqrt{5}}+\sqrt{6-2\sqrt{5}}\right)\)
\(A=\dfrac{1}{\sqrt{2}}\left(\sqrt{\left(1+\sqrt{5}\right)^2}+\sqrt{\left(\sqrt{5}-1\right)^2}\right)\)
\(A=\dfrac{1}{\sqrt{2}}\left(\left|1+\sqrt{5}\right|+\left|\sqrt{5}-1\right|\right)\)
\(A=\dfrac{1}{\sqrt{2}}\left(1+\sqrt{5}+\sqrt{5}-1\right)\)
\(A=\dfrac{2\sqrt{5}}{\sqrt{2}}=\sqrt{10}\)
Ta có: \(A^2=\left(\sqrt{10}\right)^2=10\)
\(B=\left(2+\sqrt{5}\right)^2=9+4\sqrt{5}\)
Mà: \(4\sqrt{5}>1\)
Nên: \(A^2< B^2\)
\(\Rightarrow A< B\)
Đặt \(A=\sqrt{3+\sqrt{5}}+\sqrt{3-\sqrt{5}}\)
\(=\dfrac{1}{\sqrt{2}}\left(\sqrt{6+2\sqrt{5}}+\sqrt{6-2\sqrt{5}}\right)\)
\(=\dfrac{1}{\sqrt{2}}\left(\sqrt{5}+1+\sqrt{5}-1\right)=\dfrac{2\sqrt{5}}{\sqrt{2}}=\sqrt{10}\)
=>A^2=(căn 10)^2=10=9+1
Đặt B=2+căn 5
=>B^2=(2+căn 5)^2=9+4căn 5
1<4căn 5
=>9+1<9+4căn 5
=>A^2<B^2
=>A<B
b: Ta có: \(4\sqrt{5}=\sqrt{4^2\cdot5}=\sqrt{80}\)
\(5\sqrt{3}=\sqrt{5^2\cdot3}=\sqrt{75}\)
mà 80>75
nên \(4\sqrt{5}>5\sqrt{3}\)
\(5=\sqrt{25}\)
\(2=\sqrt{3+1}=\sqrt{4}\)
\(5>\sqrt{3+1}\)
\(5=\sqrt{25}\)
\(2=\sqrt{3+1}=\sqrt{4}\)
Vậy \(5>\sqrt{3+1}\)
Nếu đúng thì bấm đúng cho mình nhé